2019
DOI: 10.3390/coatings9060383
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Behaviour of Mg0.6Ca and Mg0.6Ca2Ag Alloys with Bioactive Plasma Electrolytic Oxidation Coatings

Abstract: Bioactive Plasma Electrolytic Oxidation (PEO) coatings enriched in Ca, P and F were developed on Mg0.6Ca and Mg0.6Ca2Ag alloys with the aim to impede their fast degradation rate. Different characterization techniques (SEM, TEM, EDX, SKPFM, XRD) were used to analyze the surface characteristics and chemical composition of the bulk and/or coated materials. The corrosion behaviour was evaluated using hydrogen evolution measurements in Simulated Body Fluid (SBF) at 37 °C for up to 60 days of immersion. PEO-coated M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Determination of the size distribution, surface roughness [ 39 ], shape, and particle size [ 99 , 123 ], as well as observation of the cross-section morphology, are also possible [ 124 , 125 ]. Furthermore, similarly to SEM, TEM can be coupled with EDXS for the elemental quantification of substrates and coatings [ 126 , 127 ]. For example, an HA coating on a Ti substrate was prepared through a combination of microarc oxidation (MAO) and microwave hydrothermal treatment (MH).…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
“…Determination of the size distribution, surface roughness [ 39 ], shape, and particle size [ 99 , 123 ], as well as observation of the cross-section morphology, are also possible [ 124 , 125 ]. Furthermore, similarly to SEM, TEM can be coupled with EDXS for the elemental quantification of substrates and coatings [ 126 , 127 ]. For example, an HA coating on a Ti substrate was prepared through a combination of microarc oxidation (MAO) and microwave hydrothermal treatment (MH).…”
Section: Interaction and Morphology Studiesmentioning
confidence: 99%
“…As a result, the future focus may be on enhancing the barrier effect and binding force for a full-life corrosion-resistant service. In this regard, composite coating may be a viable option for increasing the adhesion force of organic biopolymer coating [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Furthermore, the formation of composite coatings not only improves corrosion resistance but also endows the Mg alloys with potential bioactivity and biocompatibility in long-term tests.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that the coating thickness increased with an increasing NaF concentration, which significantly reduced energy consumption [ 36 , 37 ]. Therefore, NaF as an additive in silicate-based solutions has been widely studied in the MAO process [ 38 ].…”
Section: Introductionmentioning
confidence: 99%